Survival and risk of vascular complications in myelofibrosis—A population‐based study from the Swedish MPN group. (24th June 2022) - Lindgren, Marie; Andréasson, Björn; Samuelsson, Jan; Pettersson, Helna; Enblom‐Larsson, Anneli; Ravn‐Landtblom, Anna; Scheding, Stefan; Bentham, Carolina; Ahlstrand, Erik
Abstract: Objective: To gain knowledge of underlying risk factors for vascular complications and their impact on life expectancy in myelofibrosis. Methods: From a cohort of 392 myelofibrosis patients registered in the Swedish MPN registry 58 patients with vascular complications during follow‐up were identified. Patients with vascular complications were compared with both 1:1 matched controls and the entire myelofibrosis cohort to explore potential risk factors for vascular complications and their impact on survival. Results: Incidence of vascular complications was 2.8 events per 100 patient‐years and the majority of complications were thrombotic. Patients with complications were significantly older and had lower hemoglobin when compared to the entire cohort. In the case–control analysis, no significant risk factor differences were observed. The major cause of death was vascular complications and median survival was significantly impaired in patients with vascular complications (48 months) compared to controls (92 months). Inferior survival in patients with vascular complications was found to be dependent on IPSS risk category in a Cox regression model. Conclusion: Vascular complications have a considerable impact on survival in MF. At diagnosis, risk assessment by IPSS does not only predict survival but is also associated with the risk of vascular complications.